Studi Tentang Persepsi Guru Terhadap Pendidikan Inklusi di Indonesia : Hambatan dan Peluang - Hasna Jauza Faujiyyah; Aisya Sahara; Ichsan Fauzi Rachman (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to analyze teachers’perceptions regarding inclusive education and to identify the barriers in the implementation of education policies for Children with Special Needs (CSN) in Indonesia. The method used in this research is descriptive qualitative through a literature riview that analyzes scientific literature and related policies. The results of this study indicate that although the majority of teachers support the concept of inclusive education, there are still significant obstacles in its implementation, such as the lack of teachers’ competence in handling CSN, limited training, and minimal supporting facilities. However, there are also great opportunities to strengthen the inclusive education syste, through ongoing teacher training and collaboration between schools, parents, and community. Theachers’ perceptions of Children with Special Needs (CSN) are influenced by their experiences, understanding of inclusive education, and the situations in schools. This finding concludes that the success of inclusive education healivy depends on the readliness of teachers and support from various skateholders. Therefore, i tis necessary on enchance teachers’ competencies and foster good cooperatoin on effectively implement inclusive education policies.